The word has turn. (August 2016) - Logan, Kevin
Abstract: This article positions and expands my ongoing research. This research has emerged from a cross-disciplinary practice; its purpose is to posit an intrinsic 'performativity' of the sonic within a contemporary art framework, offering new ground for an understanding of the agency of audio-works. This paper comprises a short artist statement, describing and critically situating the incorporated performative writing. The 'sonic-turn' has in recent years gained considerable purchase within broad-field humanities and contemporary art practices. This writing seeks to ally this model for theorization with a somewhat earlier conceptual paradigm, that of the 'performative-turn'. I suggest that his superimposition of the so-called 'sonic-turn' onto that of the 'performative-turn' does not merely draw attention to their close similarities, but also identifies the negative spaces and cavities left by disparity, or simple differences of form. It is this liminal space where affect, feeling, and emotion engages the quotidian through the sonic-event. Highlights: Sound has the potential to be a form of thinking and as a practice a kind of doing-thinking. Performative-writing puts the relational at centre stage, it is disposed toward deed and emergence rather than thingness. Sound design and its theories are explored through utterances and acts, employing haptic sounding as a research methodology.